SoTL inquiry in broader curricular and institutional contexts: Theoretical underpinnings and emerging trends - Hubball, Harry; Pearson, Marion L.; Clarke, Anthony (Teaching and Learning Inquiry, 2013)
Universities around the world increasingly recognize the importance of offering high quality, high-engagement student learning experiences in their undergraduate and graduate programs. While the SoTL movement and literature has gained considerable recognition and momentum over the past two decades, much less inquiry has focused on institutional and program-level educational reforms. This paper calls for a more expansive view and strategic use of SoTL inquiry in order to make substantive contributions to curriculum renewal, educational leadership practices, and, most importantly, the quality of undergraduate and graduate degree programs. Theoretical underpinnings, emerging trends, challenges, and strategic supports to enhance the effectiveness and efficiency of curricula within and across diverse disciplinary contexts are discussed.